Repetitive and stereotyped behaviors in autism spectrum disorders and frontal epilepsy: clinical case discussion. - Скрипник, Тетяна (Psychosomatic Medicine and General Practice, 2021)
Repetitive and stereotyped behaviors in autism spectrum disorders and frontal epilepsy: clinical case discussion. Tetiana Skrypnyk SI «Institute of Psychiatry, Forensic Psychiatric Examination and Monitoring of Drugs of the Ministry of Health of Ukraine», Kyiv, Ukraine Background: Autism spectrum disorders (ASD) have a prevalence of 1-2% among the world's child population and belong to the spectrum of neurodevelopmental disorders. ASD are characterized by significant genetic and clinical polymorphism, in particular comorbidity with neurological and mental disorders. In 15 - 30% of children with ASD, epilepsy is diagnosed throughout life. Repeated movements and vocalizations in ASD are often similar and require differential diagnosis with motor and vocal phenomena in the structure of epileptic seizures, with motor and vocal tics, in particular with Tourette's disorder, obsessions and compulsions in obsessive-compulsive disorder. The polymorbidity of ASD complicates the typology of recurring motor and vocal phenomena. Polymorphism of repetitive movements and vocalizations is also inherent in developmental encephalopathy. Objective : to investigate clinical polymorphism, variants of motor phenomena during 6 years of life in a child with dual diagnosis of ASD and frontal epilepsy. Materials and methods: A child with ASD and frontal focal epilepsy was observed for 6 years on the basis of the Department of Mental Disorders of Children and Adolescents of the Scientific Research Institute of Psychiatry of the Ministry of Health of Ukraine. The child underwent a comprehensive psychiatric and neurological examination every three months. For the diagnosis and assessment of the course of mental disorders, DAWBA and K-SADS-PL were used. To assess autistic symptoms, ADOS and ADI-R were used, and tics symptoms were YGTSS, and obsessive-compulsive disorders in children with ASD were CYBOCS ASD. The cognitive functioning of the child was assessed using PEP-R and the test WISC, the socially adaptive behavior of Vineland and SRS. Every six months and during unscheduled visits, an EEG study was conducted with a mathematical analysis of the results. Results: Child autism in a child was diagnosed in accordance with the ICD-10 diagnostic criteria, according to the results of a semi-structured interview with parents - ADI-R and assessment of current behavior by ADOS. During the period of controlled observation, epileptic paroxysms were characterized by the absence of complete loss of consciousness, polymorphism of seizures with numerous motor and vocal phenomena, which differentiated with symptoms of ASD, tics, obsessive-compulsive disorders. Stereotypic movements in the form of automatically repeated actions were observed in the proximal extremities, looked like a continuation and repetition of previous performed and daily performed automatic actions. The episodes of involuntary grimaces with distorted facial muscles during the first two years of observation looked like a violent act of activity, and not like epileptic paroxysms. EEG results also did not confirm the diagnosis of epilepsy. Dynamic, longitudinal monitoring of the clinical pathomorphism of repeated motor and vocal phenomena, analysis of therapeutic responses to treatment at different time periods: aripiprazole, guanfacin, sertraline, lamotrigine, analysis of symptoms that are qualified as comorbid, a gradual increase in focal epileptiform changes in the EEG allowed to diagnose frontal epilepsy with autism spectrum disorder. Conclusions: Most children with ASD have vocal and motor phenomena that may resemble symptoms of comorbid mental disorders. Repeated movements and vocalizations in ASD, as manifestations of tics, obsessive-compulsive disorders, are difficult to differentiate; they can be superimposed in the case of comorbidity disorders. With the appearance of specific epileptic activity and epileptic seizures in such patients, it is necessary to conduct differential diagnosis with developmental encephalopathy. The frontal form of epilepsy can be accompanied by seizures without complete loss of consciousness with characteristic automatic repeated stereotypic movements that have significant variability throughout life. The given clinical case supports the point of view that ASD and epilepsy are manifestations of a single pathological process - impaired neurodevelopment. Keywords: autism spectrum disorders, frontal epilepsy, repetitive and stereotyped movements, epileptic seizures.